An Exploration of Very Triangular Numbers - Baumheckel, Audrey; Forgács, Tamás (The PUMP Journal of Undergraduate Research, 2023)
We present a collection of results concerning the location and distribution of very triangular numbers among triangular numbers, including the twin very triangular number theorem, the existence of arbitrarily long gaps between – and an analog of Bertrand's postulate for – very triangular numbers.